2016
DOI: 10.1177/1044207316637546
|View full text |Cite
|
Sign up to set email alerts
|

The Standard of Proof of Intellectual Disability in Georgia

Abstract: Despite being the first state to abolish the capital punishment of defendants with intellectual disability (ID), Georgia is currently the only state to uphold what is considered to be the most stringent standard of proof of ID in the United States: beyond a reasonable doubt. Other states have implemented less stringent standards of proof (i.e., a preponderance of the evidence and clear and convincing evidence). Although the U.S. Supreme Court ruled the execution of persons with ID unconstitutional in the 2002 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, a small number of states impose a higher standard of proof, such as Arizona, which requires it be proven by clear and convincing evidence (Hollingsworth, 2007), and Georgia, which uses beyond a reasonable doubt (Hurley, 2022). Authors raised concerns about this higher standard increasing the likelihood that someone with an intellectual disability is executed because they cannot meet the standard of proof (O'Grady, 2014;Ricciardelli and Ayres, 2016;Ricciardelli and Jaskyte, 2019).…”
Section: Intellectual Disabilitiesmentioning
confidence: 99%
“…However, a small number of states impose a higher standard of proof, such as Arizona, which requires it be proven by clear and convincing evidence (Hollingsworth, 2007), and Georgia, which uses beyond a reasonable doubt (Hurley, 2022). Authors raised concerns about this higher standard increasing the likelihood that someone with an intellectual disability is executed because they cannot meet the standard of proof (O'Grady, 2014;Ricciardelli and Ayres, 2016;Ricciardelli and Jaskyte, 2019).…”
Section: Intellectual Disabilitiesmentioning
confidence: 99%
“…In January 2015, Georgia executed Warren Lee Hill. There is professional consensus that had Warren Hill been criminally tried in any other state, he would have successfully evidenced intellectual disability (Ricciardelli & Ayres, 2016). In addition to being lethal when used as a standard to evidence intellectual disability, the beyond a reasonable doubt evidentiary standard is traditionally reserved for the state to prove on the issue of guilt in a criminal court proceeding; it is thought to reflect a fundamental valuing of life and liberty (Winship, 1970).…”
Section: Unlawful Execution As Discriminatory Killingmentioning
confidence: 99%
“…However, in states that deviate from clinical standards, it cannot be known exactly to what extent persons with intellectual disability are being executed because all persons found eligible for death sentencing will not have met, as a matter of legal procedure, the state’s definition of intellectual disability. The case in point here is Georgia’s execution of Warren Lee Hill in 2015, who experts agree would have been found ineligible for execution had he lived in any other state (Ricciardelli & Ayres, 2016). Given the execution of Warren Lee Hill, there is legitimate reason to suspect that Georgia is not adequately protecting persons with intellectual disability from execution and therefore from punishments that have been ruled cruel and unusual.…”
Section: Analysis Of the Social Service Contextmentioning
confidence: 99%
“…Because Judge Allen used the calculus that he did, he concluded that Warren Hill’s noted challenges in adaptive functioning could not be evidenced to the standard of beyond a reasonable doubt—to the degree of moral certainty. Experts across the nation maintain that, had Warren Hill lived in any other state, he would have been found ineligible for execution because he would have been able to meet any of the other standards of proof (Ricciardelli & Ayres, 2016). This illustrates the importance of between-state differences, and differences on standard of proof in particular, despite the existence of federal protections.…”
Section: Introductionmentioning
confidence: 99%